Explosive detection using a novel dielectric barrier discharge ionisation source for mass spectrometry. (5th March 2018) - Fletcher, Carl; Sleeman, Richard; Luke, John; Luke, Peter; Bradley, James W.
Abstract : The detection of explosives is of crucial importance in applications such as forensic science, environmental monitoring, aviation security, and overall public safety. Mass spectrometry is typically the technique of choice for forensic analysis as it offers great sensitivity, selectivity, and speed. In this special feature perspective article, James Bradley and colleagues describe a dielectric barrier discharge plasma ionisation source capable of being coupled to many types of mass spectrometer for the rapid screening of explosives. This source operates in ambient air without the requirement for a gas flow or solvent and has an analytical surface area of approximately 540 mm 2 . The plasma produces ozone, which reacts in ambient air to form NO3 − ions. These ions form adducts which can be exploited for explosive detection. Sensitive limits of detection were achieved for four functional groups of explosives (PETN, RDX, HMTD and TNT) between 100 pg and 5 ng. James W. Bradley is Professor in the Dept. of Electrical Engineering and Electronics at the University of Liverpool (Liverpool, UK). His main research interest is in experimental and modelling studies of low temperature technological plasmas and their applications.